Shakeup Excitation during Optical Tunnel Ionization - Litvinyuk, I. V.; Légaré, F.; Dooley, P. W.; Villeneuve, D. M.; Corkum, P. B.; Zanghellini, J .; Pegarkov, A.; Fabian, C.; Brabec, T. (My University, 2005)
Shakeup of a two-electron system is investigated in the strong infrared laser field limit, both theoretically and experimentally. During tunnel ionization the electron shakes up a second electron to an excited bound state. Theoretically, a complete analytical theory of shakeup in intense laser fields is developed. We predict that shakeup produces one excited σu D+2 state in ≈105 ionization events. Shakeup is measured experimentally by using the molecular clock provided by the internuclear motion. The number of measured events is found to be in excellent agreement with theory.